Do colleges around low income areas accept more low income students? Evidence from California State Universities. Issue 7 (16th April 2019) - Chen, Li-Hsueh
ABSTRACT: Using the data of California State Universities from 2000 to 2011, this article examines whether colleges around low income areas accept more low income students. The results show that campuses around low income areas have higher access rates of students who come from families in the bottom quintile of the income distribution. No relationship is shown for other quintiles. This indicates that public universities located in low income areas have played an important role in providing access to low income students.